Suatu Tinjauan tentang Tenaga Kerja Buruh di Indonesia - Utomo, Idi Setyo (Bina Nusantara University, 2005)
Article discusses problems faced by the labor in Indonesia. To make a goodÂ relationship between companysâ€™ owner and labor, there will be an active and positiveÂ role of bipartit department in the company. In order to make an indutrial relationship isÂ in harmony in the future, it is suggested that every problem in the company should beÂ solved by the bipartit department with â€œwin-win solutionâ€.